(untitled) (Zoological Records and Reviews, 2023)
Long-term monitoring of faunal diversity provides the empirical foundation for understanding the magnitude, trajectory, and drivers of biodiversity change and for designing evidence-based conservation responses. This review synthesises evidence on long-term faunal diversity changes from monitoring programmes, resurvey studies, and historical biodiversity databases spanning the past century, with particular reference to South Asian terrestrial and freshwater ecosystems. Drawing on 184 published studies and 12 long-term monitoring datasets, we assess evidence for temporal trends in species richness, abundance, functional diversity, and community composition across major taxonomic groups. The weight of evidence confirms significant negative trends in vertebrate and invertebrate diversity globally and in South Asia, driven primarily by habitat loss, agricultural intensification, invasive species, and climate change. However, the evidence base is taxonomically and geographically uneven, with birds and mammals best-monitored and invertebrates, freshwater fauna, and soil organisms severely under-represented in long-term datasets. We identify three methodological challenges – detectability bias, spatial scale dependence, and baseline shifting – that complicate interpretation of long-term diversity trends and propose minimum standards for future long-term monitoring programmes. We conclude with a prioritised research agenda for long-term faunal diversity monitoring in South Asian ecosystems.